The Effect of Chatgpt on Students’ Language Choice in Writing Recount Text - Hutabarat, Esra Delima; Napitupulu, Selviana (Journal of English Language Teaching and English Linguistics, 2026)
Writing is an essential skill in English learning that requires accuracy, coherence, and appropriate language use. However, many junior high school students experience difficulties in selecting suitable language when writing recount texts. This study aimed to examine the effect of ChatGPT on students’ language choice in writing recount texts at the eighth grade of SMP Negeri 1 Pematangsiantar. A quantitative approach with a pre-experimental one-group pre-test and post-test design was employed. The sample consisted of 24 students selected through purposive sampling. A writing test was administered to assess students’ language choice focusing on vocabulary use, grammatical accuracy, sentence structure, and mechanics. The data were analyzed using descriptive statistics and a paired-sample t-test. The findings revealed that the mean score increased from 52.92 in the pre-test to 86.75 in the post-test, with a mean difference of 33.83 points. The t-test result showed a statistically significant improvement after the use of ChatGPT. Therefore, it can be concluded that ChatGPT has a positive effect on students’ language choice in writing recount texts. Keywords: ChatGPT, Language Choice, Recount Text, Writing Skill